Tailoring the Reversible Phase Transition of Perovskite Nanofiber Electrodes for High-Performance and Durable Reversible Solid Oxide Cells - Chaofan Yin; Jiaming Yang; Jiangyuan Feng; Yueyue Sun; Zhengrong Liu; Junkai Wang; Jiajia Cui; Zixuan Xue; Liang Zhang; Yucun Zhou; Jun Zhou; Liangfei Xu; et al. (Nano-Micro Letters)
Highlights La0.3Sr0.6Ti0.1Co0.2Fe0.7O3−δ (LSTCF) nanofibers showed high structural reversibility. LSTCF fibers and CoFe nanoparticles were reconstructed through a reversible phase transition process. The LSTCF fiber electrode demonstrated excellent activity and stability for power and fuel co-generation.